Frequent and Persistent Salivary Gland Ectasia and Oral Disease After COVID-19. (May 2021) - Gherlone, E.F.; Polizzi, E.; Tetè, G.; De Lorenzo, R.; Magnaghi, C.; Rovere Querini, P.; Ciceri, F.
The clinical picture of coronavirus disease 2019 (COVID-19) in various target organs has been extensively studied and described. However, relatively little is known about the characteristics of oral cavity involvement. This is surprising, considering that oral mucosal and salivary gland cells are known targets for the direct replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and that the presence of the virus in saliva is a source of transmission of the infection. The aim of our study was to investigate the presence and prevalence of oral manifestations in COVID-19 survivors. We profiled the oral involvement in 122 COVID-19 survivors that were hospitalized and followed up at a single-referral university hospital in Milan, Italy, between July 23, 2020 and September 7, 2020, after a median (interquartile range) time from hospital discharge of 104 (95 to 132) d. We found that oral manifestations, specifically salivary gland ectasia, were unexpectedly common, with oral manifestations being detected in 83.9% while salivary gland ectasia in 43% of COVID-19 survivors. Salivary gland ectasia reflected the hyperinflammatory response to SARS-CoV-2, as demonstrated by the significant relationship with C-reactive protein (CRP) and lactate dehydrogenase (LDH) levels at hospital admission, and with the use of antibiotics during acute disease. Both LDH levels and antibiotic administration survived as independent predictors of salivary gland ectasia at multivariable analysis. Temporomandibular joint abnormalities, facial pain, and masticatory muscle weakness were also common. Overall, this retrospective and prospective cohort study of COVID-19 survivors revealed that residual damage of the oral cavity persists in the vast majority of patients far beyond clinical recovery, and suggests that the oral cavity represents a preferential target for SARS-CoV-2 infection. Further studies are needed to clarify the connection between SARS-CoV-2 infection and oral disorders.